Interconnected molybdenum disulfide@tin disulfide heterojunctions with different morphologies: a type of enhanced counter electrode for dye-sensitized solar cells. Issue 9 (9th February 2018) - Zhang, Kang; Yao, Jixin; Zuo, Xueqin; Yang, Qun; Tang, Huaibao; Li, Guang; Wu, Mingzai; Zhu, Kerong; Zhang, Haijun
Abstract : The MoS2 @SnS2 heterojunctions have been synthesized and displayed the enhanced performance due to the specific crystal structure. Abstract : In this work, we successfully synthesized SnS2 nanoparticles, a hollowed-out netty MoS2 (nMoS2 ) nanostructure, a flower-like MoS2 (fMoS2 ) nanostructure, an nMoS2 @SnS2 heterostructure, and an fMoS2 @SnS2 heterostructure via a simple and facile hydrothermal process. We used powder X-ray diffractograms to verify purity and crystalline phases of the as-prepared samples. Additionally, the structures and morphologies of as-prepared components were checked by X-ray photoelectron spectroscopy analysis (XPS), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). A dye-sensitized solar cell (DSSC) assembled with this original heterostructure as a counter electrode (CE) displayed a splendid power conversion efficiency (PCE) of 7.63% along with stable catalytic performance for triiodide reduction. This is better than other DSSCs including: SnS2 CE (6.67%), nMoS2 CE (5.78%), fMoS2 CE (5.37%), and fMoS2 @SnS2 CE (7.08%). According to our experimental results, we believe that the outstanding performance of nMoS2 @SnS2 heterostructures for a DSSC is because of their characteristic crystal structure, which may contribute to playing a heterogeneous and synergistic effect between the active materials, optimize dispersity of the samples, avoid recombination of electron–hole pairs to accelerate velocity of triiodide reduction, and enhance stability in a I3 − /I − electrolyte. Hence, the nMoS2 @SnS2 heterostructure can play a better role in DSSCs with excellent performance and superior stability as an efficient CE.